2019
DOI: 10.1002/hbm.24843
|View full text |Cite
|
Sign up to set email alerts
|

Fear in dreams and in wakefulness: Evidence for day/night affective homeostasis

Abstract: Recent neuroscientific theories have proposed that emotions experienced in dreams contribute to the resolution of emotional distress and preparation for future affective reactions. We addressed one emerging prediction, namely that experiencing fear in dreams is associated with more adapted responses to threatening signals during wakefulness. Using a stepwise approach across two studies, we identified brain regions activated when experiencing fear in dreams and showed that frightening dreams modulated the respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 94 publications
4
49
1
Order By: Relevance
“…Beyond confirming the hypothesized impact of both daily emotional experience and sleep pattern on the oneiric activity during the lockdown also considering its emotional features, such finding can also be considered in light of the hypothesis that dreams may have a role in emotional processing and memory consolidation [ 53 ]. Dreaming activity and emotional regulation share similar neurobiological processes, suggesting the existence of a continuum between waking and REM sleep activity in several areas like amygdala, hippocampus and medial prefrontal cortex [ 18 , 20 , 24 , 72 , 70 ]. Consistently, it has been proposed that dreams may represent an offline simulation of threatening events, working as problem-solving based emotional coping strategies for the rehearsal of threat-avoidance skills, sustained by the activation of amygdalocortical networks associated with fear (Revonsuo, 200; [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond confirming the hypothesized impact of both daily emotional experience and sleep pattern on the oneiric activity during the lockdown also considering its emotional features, such finding can also be considered in light of the hypothesis that dreams may have a role in emotional processing and memory consolidation [ 53 ]. Dreaming activity and emotional regulation share similar neurobiological processes, suggesting the existence of a continuum between waking and REM sleep activity in several areas like amygdala, hippocampus and medial prefrontal cortex [ 18 , 20 , 24 , 72 , 70 ]. Consistently, it has been proposed that dreams may represent an offline simulation of threatening events, working as problem-solving based emotional coping strategies for the rehearsal of threat-avoidance skills, sustained by the activation of amygdalocortical networks associated with fear (Revonsuo, 200; [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, it has been proposed that dreams may represent an offline simulation of threatening events, working as problem-solving based emotional coping strategies for the rehearsal of threat-avoidance skills, sustained by the activation of amygdalocortical networks associated with fear (Revonsuo, 200; [ 51 ]. Other authors propose a role for dreams in fear extinction [ 45 , 70 ], emotional conflict resolution, and reduction of negative mood [ 10 ]. Beyond the specific focus of these theoretical models, they all suggest that fear in dreams should be related to more adaptive behaviours in response to daily threatening stimuli [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear was the least well-identified emotion (53%). Recent researches, including functional MRI, reported that the insular cortex plays a main role in the identification and reaction to fear 34 , 35 . Complex mental and cognitive states accurately was attributed in 85% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating cortical activity during non-REM, REM and SI in the rock hyrax with high density electroencephalography, as employed by Siclari et al (2017) in humans which is predictive of dreams in humans, or other methods under development in humans to understand dream content (e.g. Horikawa, Tamaki, Miyawaki, & Kamitani, 2013;Sterpenich, Perogamvros, Tononi, & Schwartz, 2019), may augment our understanding of the neural correlates of consciousness in humans and across mammals as a class. The comparative observations regarding the physiology of sleep, and by extensions dreams, in mammals thus provides not only interesting observations for thought experiments, but also reveals potentially informative model species that may rapidly increase our current understanding of the manner in which the brain produces, processes, and accesses conscious experiences.…”
Section: Discussionmentioning
confidence: 99%